Cytogenetically Elusive Sex Chromosomes in Scincoidean Lizards - Kostmann, Alexander; Augstenová, Barbora; Frynta, Daniel; Kratochvíl, Lukáš; Rovatsos, Michail (International journal of molecular sciences, 2021)
The lizards of the species-rich clade Scincoidea including cordylids, gerrhosaurids, skinks, and xantusiids, show an almost cosmopolitan geographical distribution and a remarkable ecological and morphological divergence. However, previous studies revealed limited variability in cytogenetic traits. The sex determination mode was revealed only in a handful of gerrhosaurid, skink, and xantusiid species, which demonstrated either ZZ/ZW or XX/XY sex chromosomes. In this study, we explored the karyotypes of six species of skinks, two species of cordylids, and one gerrhosaurid. We applied conventional and molecular cytogenetic methods, including C-banding, fluorescence in situ hybridization with probes specific for telomeric motifs and rDNA loci, and comparative genomic hybridization. The diploid chromosome numbers are rather conserved among these species, but the chromosome morphology, the presence of interstitial telomeric sequences, and the topology of rDNA loci vary significantly. Notably, XX/XY sex chromosomes were identified only in Tiliqua scincoides, where, in contrast to the X chromosome, the Y chromosome lacks accumulations of rDNA loci. We confirm that within the lizards of the scincoidean clade, sex chromosomes remained in a generally poor stage of differentiation.
Keywords: comparative genome hybridization; Sex Chromosomes; Male; pohlavní chromozomy; karyotypizace; srovnávací genomová hybridizace; hybridizace in situ fluorescenční; Sex Determination Processes; telomeres; sex determination; ribozomální DNA; Karyotyping; heterochromatin; molekulární evoluce; Evolution, Molecular; mužské pohlaví; rDNA; Lizards; ještěři; FISH; reptiles; Animals; sex chromosomes; ženské pohlaví; fluorescence in situ hybridization; evolution; zvířata; Comparative Genomic Hybridization; Diploidy; In Situ Hybridization, Fluorescence; CGH; DNA, Ribosomal; procesy určující pohlaví; Female; diploidie; cytogenetické vyšetření; karyotype; Cytogenetic Analysis